Efficacy and safety of abobotulinumtoxinA for upper limb spasticity in children with cerebral palsy: a randomized repeat‐treatment study. (18th November 2020) - Delgado, Mauricio R; Tilton, Ann; Carranza‐Del Río, Jorge; Dursun, Nigar; Bonikowski, Marcin; Aydin, Resa; Maciag‐Tymecka, Iwona; Oleszek, Joyce; Dabrowski, Edward; Grandoulier, Anne‐Sophie; Picaut, Philippe; ,
Abstract : Aim: To assess the efficacy and safety of repeat abobotulinumtoxinA injections in reducing upper limb spasticity in children with cerebral palsy (CP). Method: This was a double‐blind, repeat‐cycle study (NCT02106351) in children with CP (2–17y). Children were randomized to receive 2U/kg (control), 8U/kg, or 16U/kg abobotulinumtoxinA injections into the target muscle group (wrist or elbow flexors) and additional muscles alongside occupational therapy via a home‐exercise therapy program (HETP; minimum five 15min sessions/wk). Children received 8U/kg or 16U/kg plus HETP in cycles 2 to 4. Results: During cycle 1, 210 children (126 males, 84 females; mean age [SD] 9y [4y 5mo], range 2–17y; n =70/group) had at least one upper limb abobotulinumtoxinA injection and 209 complied with the HETP. At week 6 of cycle 1, children in the 8U/kg or 16U/kg groups had significantly lower Modified Ashworth scale scores versus the 2U/kg group (primary outcome: treatment differences of –0.4 [ p =0.012] and –0.7 [ p <0.001] respectively). All groups improved on Physician Global Assessment and children in all groups achieved their treatment goals at least as expected. Therapeutic benefits were sustained during cycles 2 to 4; muscular weakness was the only treatment‐related adverse event reported in at least one child/group (4.3% and 5.7% vs 1.4% respectively). Interpretation: Treatment with 8U/kg or 16U/kg abobotulinumtoxinA significantly reduced upper limb spasticity versus the 2U/kg control dose. Therapeutic benefits of abobotulinumtoxinA plus HETP were sustained with repeat treatment cycles. What this paper adds: AbobotulinumtoxinA injections significantly reduced upper limb spasticity in children with cerebral palsy. Children treated with abobotulinumtoxinA and targeted home exercises showed global improvement and goal attainment. Benefits were sustained over 1 year with repeat cycles of abobotulinumtoxinA and home exercises. AbobotulinumtoxinA injections into the upper limb were well tolerated over 1 year. What this paper adds: AbobotulinumtoxinA injections significantly reduced upper limb spasticity in children with cerebral palsy. Children treated with abobotulinumtoxinA and targeted home exercises showed global improvement and goal attainment. Benefits were sustained over 1 year with repeat cycles of abobotulinumtoxinA and home exercises. AbobotulinumtoxinA injections into the upper limb were well tolerated over 1 year. This article is commented on by Graham on page 499 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Eficacia y seguridad de abobotulinumtoxinA para la espasticidad de las extremidades superiores en niños con parálisis cerebral: un estudio aleatorizado de repetición del tratamiento: Objetivo: Evaluar la eficacia y seguridad de las inyecciones repetidas de abobotulinumtoxinA para reducir la espasticidad de las extremidades superiores en niños con parálisis cerebral (PC). Método: Este fue un estudio doble ciego de ciclo repetido (NCT02106351) en niños con PC (2‐17 años). Los niños fueron aleatorizados para recibir inyecciones de abobotulinumtoxinA de 2U / kg (control), 8U / kg o 16U / kg en el grupo de músculos objetivo (flexores de la muñeca o del codo) y músculos adicionales junto con la terapia ocupacional a través de un programa de terapia de ejercicio en el hogar (HETP; mínimo cinco sesiones de 15min / semana). Los niños recibieron 8U / kg o 16U / kg más HETP en los ciclos 2 a 4. Resultados: Durante el ciclo 1, 210 niños (126 varones, 84 mujeres; edad media [DE] 9 años [4 años 5 meses], rango 2‐17 años) (n = 70 / grupo) recibieron al menos una inyección de abobotulinumtoxinA en el miembro superior y 209 cumplieron con la HETP. En la semana 6 del ciclo 1, los niños de los grupos de 8U / kg o 16U / kg tenían puntuaciones de la escala de Ashworth modificadas significativamente más bajas en comparación con el grupo de 2U / kg (resultado primario: diferencias de tratamiento de –0, 4 [p = 0, 012] y –0, 7 [p <0, 001] respectivamente). Todos los grupos mejoraron en la escala Evaluación Global del Médico, y los niños de todos los grupos lograron sus objetivos de tratamiento al menos como se esperaba. Los beneficios terapéuticos se mantuvieron durante los ciclos 2 a 4; la debilidad muscular fue el único evento adverso relacionado con el tratamiento informado en al menos un niño / grupo (4, 3% y 5, 7% frente a 1, 4% respectivamente). Interpretación: El tratamiento con 8U/kg o 16U/kg de abobotulinumtoxinA redujo significativamente la espasticidad de las extremidades superiores en comparación con la dosis de control de 2U/kg. Los beneficios terapéuticos de abobotulinumtoxinA más HETP se mantuvieron con ciclos de tratamiento repetidos. Eficácia e segurança da abobotulinumtoxina A para espasticidade do membro superior em crianças com paralisia cerebral: um estudo randomizado de tratamento repetido: Objetivo: Avaliar a eficácia e segurança de injeções repetidas de abobotulinumtoxina A na redução da espasticidade do membro superior em crianças com paralisia cerebral (PC). Método: Este foi um estudo duplo cego, com ciclo repetido (NCT02106351) em crianças com PC (2–17a). As crianças foram randomizadas para receber injeções de 2U/kg (controle), 8U/kg, ou 16U/kg de abobotulinumtoxina A no grupo muscular alvo (flexores de punho ou cotovelo) e músculos adicionais junto com um programa de terapia ocupacional com exercícios domiciliares (PTOED; mínimo de 5 sessões/semana de 15 minutos). As crianças receberam 8U/kg ou 16U/kg mais PTOED em ciclos de 2 a 4. Resultados: Durante o ciclo 1, 210 crianças (126 do sexo masculino, 84 do sexo feminino; media de idade [DP] 9a [4a 5m], variação 2–17a) ( n =70/grupo) tiveram ao menos uma injeção de abobotulinumtoxina A no membro superior e 209 seguiram o PTOED. Na semana 6 do ciclo1, crianças nos grupos 8U/kg ou 16U/kg tiveram escores da escala Ashworth significativamente menores versus o grupo 2U/kg (desfecho primário: diferenças no tratamento de –0, 4 [ p =0, 012] e –0, 7 [ p <0, 001] respectivamente). Todos os grupos melhoraram na Avaliação Médica Global e crianças de todos os grupos atingiram os objetivos de tratamento pelo menos como esperado. Benefícios terapêuticos foram mantidos durante os ciclos 2 a 4; fraqueza muscular foi o único evento adverso relacionado ao treinamento em pelo menos uma criança/ grupo (4, 3% e 5, 7% vs 1, 4% respectivamente). Interpretação: O tratamento com 8U/kg ou 16U/kg de abobotulinumtoxina reduziu significativamente a espasticidade do membro superior versus a dose controle de 2U/kg. Benefícios terapêuticos da abobotulinumtoxina A mais PTOED foram mantidos com os repetidos ciclos de tratamento.